Extended flexible capacity planning methodology with flight network contribution to the airline fleet assignment problem - Enki, Yusuf; Ozkir, Vidan; Sen, Ceyda; Ciftci, Muharrem Enis (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Flexible capacity planning is crucial for the airline industry due to the high fixed cost of assets, notably aircraft ownership, and the fluctuating demand, particularly in response to external shocks like pandemics and political crises. Following the negative consequences of such events on the financial positions of almost all airline companies, there is growing interest in developing more responsive capacity planning structures for cost efficiency in the airline industry. In this study, we present a sequential two-phase methodology for flexible capacity planning and airline fleet assignment considering the factors related to fleeting strategies, passenger demand behavior, and contribution of flights in the network. The first phase of the methodology generates potential scenarios to estimate the number of flights to the destinations, based on the data and the reports provided by two prominent associations in the aviation industry, which incorporate various country-related and airline-related factors, including population, income, routes, airports, and connectivity. The second phase identifies the required number of aircraft for each type within the fleet inventory, taking into account the aircraft utilization rates associated with each scenario. The fleet assignment problem is also reformulated to employ the objective of maximizing total profit of the entire flight network by introducing network contribution and nation/regionspecific limitations in this phase. A real case study from Turkey is conducted to illustrate efficiency of the proposed methodology. We also present a comparative study to highlight the impact of network contribution and how fleet size affects the outcomes. We have observed that the inclusion of the network contribution aspect and country constraints has led to a significant improvement in financial indicators and connectivity. The results show that the methodology can effectively tackle challenges in airline transportation problems.
Keywords: Airline fleet assignment problem; Airline planning; Network contribution; Network profitability; Airline capacity planning; Demand projection; LOW-COST CARRIERS; NEIGHBORHOOD SEARCH; SOLUTION ALGORITHMS; POLYHEDRAL ANALYSIS; SCHEDULE DESIGN; DEMAND MODEL; PASSENGER; OPTIMIZATION; Computer Science; Engineering; Operations Research & Management Science